2021
DOI: 10.3389/fpsyg.2021.635158
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Consequences of Adversity in Australia: National Bushfires Associated With Increased Depressive Symptoms, While COVID-19 Pandemic Associated With Increased Symptoms of Anxiety

Abstract: High quality monitoring of mental health and well-being over an extended period is essential to understand how communities respond to the COVID-19 pandemic and how to best tailor interventions. Multiple community threats may also have cumulative impact on mental health, so examination across several contexts is important. The objective of this study is to report on changes in mental health and well-being in response to the Australian bushfires and COVID-19 pandemic. This study utilized an Experience-Sampling-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Furthermore, the lack of social support and community belonging moderated the relationship between trauma and sleep disorders [ 13 ]. Notably, a recent study confirmed the importance of social interaction and how this has changed as a result of COVID-19 compromising mental health conditions such as depression and anxiety [ 63 ]. This is reflective of the impact of collective trauma, referred to earlier in this review [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lack of social support and community belonging moderated the relationship between trauma and sleep disorders [ 13 ]. Notably, a recent study confirmed the importance of social interaction and how this has changed as a result of COVID-19 compromising mental health conditions such as depression and anxiety [ 63 ]. This is reflective of the impact of collective trauma, referred to earlier in this review [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality declined globally (Gupta et al, 2020;Pérez-Carbonell et al, 2020). People stayed inside under a relentless assault of bad news: police brutality and widespread civil unrest (Taylor, 2021), months-long and devastating wildfires (Arjmand et al, 2021), chronic resource shortages and skirmishes over toilet paper (Labad et al, 2021), reports of giant invasive hornets (Higgins, 2020), announcement of unavoidable climate consequences (McGrath, 2021), and mounting evidence that our online social lives have been manipulated with harmful intent (Hatmaker, 2021;Ortutay, 2021). The state of the world, apparently, keeps getting worse.…”
Section: We Need Vret + Tmh For the Other Pandemicmentioning
confidence: 99%
“…The ‘Black Summer’ bushfires were responsible for the direct deaths of 33 people and the indirect deaths of more than 450 people who died due to smoke inhalation (Bradstock et al, 2021 ; Cook et al, 2021 ; Hitch, 2020 ). With more than a billion animals killed and 18.6 million hectares of land burnt, the Australian public, including school aged-children, entered the COVID-19 pandemic with significantly increased rates of depression and concern about the future (Arjmand et al, 2021 ). The closure of schools, with its loss of connection, emotional support, and stability for children and families (Brown et al, 2020 ) was, therefore, part of a cumulatively stressful period for the nation.…”
Section: Introductionmentioning
confidence: 99%